MENTAL BULLYING AND ITS IMPACT TO VICTORIA DAWSON IN DANIELLE STEEL’S BIG GIRL - KARINA RACHMAWATI (LITERA KULTURA : Journal of Literary and Cultural Studies, 2014)
MENTAL BULLYING AND ITS IMPACT TO VICTORIA DAWSON IN DANIELLE STEEL’S BIG GIRL Karina Rachmawati English Literature, Faculty of Languages and Arts, Surabaya State University rahmakarina92@gmail.com Prof. Dr. FD Kurnia, M.Pd. English Department, Faculty of Languages and Arts, Surabaya State University Abstrak Novel Big Girl adalah novel Danielle Steel yang mempunyai tema Mental Bullying dalam penulisannya. Victoria Dawson mental bullying menjadi topic utama dalam penelitian ini. Dengan demikian penelitian ini berfokus pada tiga masalah utama (1) Mental Bullying seperti apa yang dialami oleh Victoria Dawson dalam novel Big Girl oleh Danielle Steel (2) Penyebab Victoria Dawson Mental Bullying dalam novel Big Girl oleh Danielle Steel (3) Dampak Victoria Dawson Mental Bullying dalam novel Big Girl oleh Danielle Steel. Data dari tesis ini diambil dari novel sebagai sumber utama dan membaca intensif untuk langkah analisis berikutnya. Untuk menjawab semua masalah, penelitian ini menggunakan teori Psychology of Bullying untuk menggambarkan Mental Bullying, Penyebab dan Dampaknya. Penelitian kepustakaan digunakan untuk data yang dibutuhkan perguruan tinggi. analisis yang digunakan untuk menganalisis data yang dikumpulkan berdasarkan teori. Deskripsi digunakan untuk menjelaskan hasil analisis. Setelah melalui analisis yang panjang dengan menggunakan tiga macam metode di atas,Ditemukan bahwa mental bullying membawa dampak buruk bagi korban bullying karena menggunakan kata kata dan emosi untuk menghina seseorang. Korban mental bullying mengalami depresi, merasa takut, dan merasa kesepian untuk bergaul dengan orang lain dan sebagian besar dari mereka tidak mempunyai teman. Kata kunci: Bullying, Mental Bullying, Insult Abstract Big Girl is Danielle steel’s novel which has Mental Bullying themes she writes on throughout her work. Victoria Dawson mental bullying has become the main topic of this study. Thus this study focuses on three major problems, (1) What mental bullying is experienced by Victoria Dawson in Danielle Steel’s Big Girl, (2) What are the causes of Victoria Dawson mental bullying in Danielle Steel’s Big Girl, and (3) What are the impacts of Victoria Dawson mental bullying in Danielle Steel’s Big Girl. The data of the thesis is taken from the novel as the main source and intensive reading to next step of analysis. To answer the all problems, this study is using Psychology of Bullying Theory to depict the mental bullying, causes and impacts. This study also used library research, analysis and description. Library research is used to college data needed. An analysis is used to analyze the collected data based on the theories. Description is used to describe the result of analysis. After getting through long analysis by using three kinds of method above, it finds out that mental bullying bring bad impacts to victim of bullying because using words and emotions to insult someone. The mental victims of bullying are depressed, always feeling afraid and feel lonely to associate with other people and most of them has not a friend. Key words: Bullying, Mental Bullying, Insult. INTRODUCTION Many people may probably had problems. One of their problems related with psychological. Psychology term is a thing that can not be separated far from human life. Psychology terms have touched all of the aspect about human life. Everything about human life’s conflict has always touched the deepest side of human’s psychology condition. There must be something that related to the psychology. When somebody gets the hurt from anything, there is always a big possibility of one who get the messy thing in his mind; it could influence his internal condition such as his way of thinking, his emotional reaction, etc. For the most serious effect, they might get the trauma and also the death of somebody because they can not control the internal conflict inside their soul. One of psychological experiences in this paper is Bullying. Bullying is a serious issue that is faced by many people, and can leave a people to live in complete fear. Bullying it self mean typically a form of repeated, persistent and aggressive behaviour directed at an individual or individuals that is intended to cause (or should be known to cause) fear and distress and/or harm to another person’s body, feelings, self-esteem or reputation. Bullying occurs in a context where there is a real or perceived power imbalance. Bullying is the use of force to intimidate someone. It can happen to anyone, anywhere and any time. It can come from a single person or a group. Bullying can be delivered verbally or in some extreme cases physically where the victim suffers actual bodily harm. Bullying behavior can be direct or indirect bullying. Direct bullying behaviors (overt) involve behaviors that are observable and that are usually expressed by physical and verbal means. Usually direct bullying involves relatively open attacks on a victim and are “in front of your face” behaviors. However, bullying behavior is not always hitting, kicking, teasing, or name calling. Children who bully others may use subversive acts that hurt just as much, but are harder to detect. Indirect bullying is related with Mental Bullying. This bullying practice occurs secretly and in the outside of our monitoring radar. Examples of indirect bullying are leaving others out on purpose, spreading rumours to destroy another’s reputation or getting others to dislike another person, a cynical viewing, public humiliating, isolating, humiliating, accusing, gossiping, slandering, snapping, glaring and pouting.. This is covert bullying or “behind your face” behaviours. Bullying is not just a childhood problem: it extends to adulthood, the boardroom, shop floor and the dysfunctional family. (Beane, 2003:6). It can be concluded that bullying related with mental abuse, also known as mental bullying. Mental Bullying can occur in close relationships, including parent/child relationships, marital relationships or sibling relationships. Mental bullying causes damage in the victim as she is made to believe she is worthless and at fault. Mental bullying is particularly harmful on children because of the impact it has on developing self-esteem and patterns relating to others. As mentioned above, one of the novels deals with theme Mental Bullying is Big Girl, because this study will describe about Victoria Dawson mental bullying is the main topic of Big Girl, because it’s interesting for discussed through topic. Victoria Dawson experienced mental bullying when the firstborn child, she grows up out of place in her family because of her fair hair and thicker build. While the rest of her family is dark haired and thin, Victoria is blond, blue-eyed and according to her father, has his grandmother’s ‘big’ build. Victoria puts up with her father’s thinly-veiled barbs while her mother constantly drops weight remarks. Meanwhile her parents dote on the younger sister Grace, as she is beautiful and thin. In accordance of background study above, it can be simplify to discuss among three problems that emerge as significant concern toward this novel. 1. What mental bullying is experienced by Victoria Dawson in Danielle Steel’s Big Girl? 2. What are the causes of Victoria Dawson mental bullying in Danielle Steel’s Big Girl? 3. What are the impacts of Victoria Dawson mental bullying in Danielle Steel’s Big Girl? This study will uses Psychology of Bullying theory in order to answer the question in the statement of the problems, this study tries applying theory as the base of analysis this theory is: Psychology of bullying to analyze about Victoria Dawson Mental Bullying in Danielle Steel’s Big Girl. The first problem is what mental bullying is experienced by Victoria Dawson in Danielle Steel’s Big Girl. This statement will use Psychology of bullying theory. with several kinds of mental bullying are; public humiliating, isolating, accusing, gossiping, slandering, snapping, embarrassed, humiliated and condescended. But of the several kinds mental bullying that have been mentioned above, which includes kinds of mental bullying that occurred and depicted to Victoria mental bullying are humiliation; embarrassed and condescended. Then the second is what are the causes of Victoria Dawson mental bullying in Danielle Steel’s Big Girl. This statement will use Psychology of Bullying theory. The causes of Victoria Dawson mental bullying its come from Family factor, There are two causes that made Victoria experienced Mental Bullying from family factor; Narcissistic her parents and Being Different from her Family. And the last is What are the impacts of Victoria Dawson mental bullying in Danielle Steel’s Big Girl. This statement will use Psychology of Bullying theory. The impacts of Victoria Dawson mental bullying its she feel sadness and self esteem which is there are three impacts because of Victoria feel sadness and self esteem; Search for Self Identity to New York, Struggle from her Body Image, and See a Psychiatrist. RESEARCH METHOD This thesis is regarded as a descriptive-qualitative study and use a library research. Therefore, the data will not be in number. The descriptive method of his study can be elaborated as follows. The main source of the study is taking from Danielle steel novel entitled Big Girl by Danielle steel, is an American novelist who is currently the bestselling author alive and the fourth bestselling author of all time, with over 800 million copies sold. Based in California for most of her career, Steel has produced several books a year, often juggling up to five projects at once, all her novels have been bestsellers, including those issued in hardback. Big Girl published by Delacorte Press on February 23, 2010. In analyzing the data, a descriptive qualitative method was applied. The data mostly got from library research. The data consist of the main data and additional data. The main data are collected or taken from Danielle Steel’s Big Girl in the form of quotations, comments on the events and action related with the issue that is Victoria Dawson mental bullying, the causes and the Impacts of Victoria Dawson mental bullying in Big Girl. The supporting data are taking from many sources such as articles, reference books, journals, magazines, internet sources that are relevant with the topic and other related sources. Then the data are collected, clarified, analyzed and made a conclusion. To assist and strengthen the data will be analyze; Victoria Dawson mental bullying in Danielle Steel’s Big Girl used Psychology of bullying, the causes and the impacts of Victoria Dawson mental bullying. Overall, those concepts are relating with the Victoria characterization in her life. This study contains four chapters. The first chapter is about introduction consist of background of the study, statement of the problem, purpose of the study, significance of the study, limitation of the study, research method and organization of the study. The second chapter is Review related of literature; consist of Psychology of bullying, Victoria Dawson mental bullying, the causes and the impacts of Victoria Dawson mental bullying, and paradigm of analysis. The third chapter is analysis about the novel Big Girl. The fourth or the last chapter in this study is conclusion of the analysis. This study encloses appendices: the biography of Danielle Steel and the synopsis of Big Girl. ANALYSIS Which the theories that are state in the previous chapter are used as a guide to accomplish it. This analysis will divided into several sub chapters. The first part in this chapter is about the Mental Bullying is experienced by Victoria Dawson in Danielle Steel’s “Big Girl”. The second part is about the causes of Victoria Dawson mental bullying and the last chapter about the impacts of Victoria Dawson mental bullying in the novel. Victoria Dawson Mental Bullying Bullying is emotional negative action performed against others who have traits that differ from other large groups, for example, of different races, shapes hair, skin color and so on. Bullying can be emotional done by cursing or acting intentionally using motion - a particular movement aimed to insult. (Elliot , 2005:2). One of kind bullying is related with mental abuse, and usually called with mental bullying. According to Sejiwa, (2007:2) mental bullying is a type of bullying. It is one of the most hurtful types of bullying. It is the act of using words and emotions to hurt someone. Mental bullying has two types, Verbal and Emotional. In this part it will discuss about Victoria Dawson mental bullying. To depict Victoria mental bullying, it uses Psychology of Bullying theory, with several kinds of mental bullying are; public humiliating, isolating, accusing, gossiping, slandering, snapping, embarrassed, humiliated and condescended. But of the several kinds mental bullying that have been mentioned above, which includes kinds of mental bullying that occurred and depicted to Victoria mental bullying are: Humiliation Humiliation is a kind of mental bullying that depicted to Victoria Dawson mental bullying. Big Girl tells about Victoria Dawson as the main character, she experienced mental bullying from her parents and people around her because different physical appearance than her family. Victoria parents were born from perfect physical appearance. Her father, mother and sister have the same appearance, but Victoria was different. When Victoria was a child, she experienced mental bullying from people around her and especially from her parents. In Victoria Dawson mental bullying is found quotations to depicted humiliation as kind of mental bullying. Victoria Dawson is an outcast in her own family, the round peg in a family of square holes. It is precisely her roundness that marks her as an outsider. Chubby, blond and blue-eyed in a family of slim, dark stunners, she is the daughter whom her father called "the tester cake," before getting the recipe right with younger daughter Gracie. When Victoria had a sister, Grace born with perfect physique appearance and Victoria parents satisfied with grace born. Jim always said to Victoria that she was a little tester cake. It can be seen from the quotation here: “I guess you were our little tester cake,” he said, “This time we got the recipe just right,” he commented happily.” (p. 20) The quotation shows that Victoria is tester cake for her parent, because Victoria did not have beautiful appearance liked her parents. It made Victoria suddenly terrified that because Grace had come out so perfectly, maybe they would throw her away. She thought of what her father had said then about her being the tester cake, and wondered if it was true. Maybe they had only had her to make sure they got it right with Grace. And by then, her father still regularly teased her about being their “tester cake.” Victoria knew exactly what that meant, that Grace was beautiful and she wasn’t, and they had gotten it right the second time around. And her father always introduced Victoria to a business associate as his tester cake, but he also said he as proud of her, more than once, which surprised Victoria, since she never really thought that her father was proud of her. Embarrassed Embarrassed is also a kind of mental bullying that depicted to Victoria Dawson mental bullying. embarrassed occurs to others who have traits that differ from other groups or society, for example, of different races, shapes hair, skin color and so on. In this novel Victoria Dawson embarrassed by her parents and society because she had different physical appearance from her parents, she was a blond-haired, blue-eyed, chubby little girl; the complete opposite of her tall, slim, and beautiful parents. She resembled her paternal great-grandmother. She was viewed as a disappointment to her parents. Her father always referred as Queen Victoria. It can be seen from quotation here: “Jim always commented that she’d been named for Queen Victoria, whom she looked like, and then laughed heartily. It became his own favorite joke about the baby, which he was more than willing to share.” (p. 10) From the quotation above, the reader know that Jim, he had perfect appearances unsatisfied with his child, Victoria. He always said that Victoria looked like Queen Victoria because she had bad appearance. And it is became his own favorite joke and he liked to share with other people. He reveals unsatisfied feeling to Victoria used jokes that made Victoria feel sad. Condescended And the last kind of mental bullying besides humiliation and embarrassed that depicted to Victoria Dawson mental bullying is condescended. Nobody likes to be condescended; when condescending person is increased endlessly it would make someone feel frustrating, annoying and humiliating. In this novel Victoria parents condescending Victoria about her physical appearance and her job and some quotations will be explained about Victoria condescending. When Victoria decided moves to New York and she want become a teacher, Victoria's choice of profession was also a source of displeasure for her father and he often told her she could do better. Victoria was a teacher for high school seniors in a prestigious private school in New York City. Instead of being proud of her as he should, her father constantly reminded her that she should get a "real job" in the business world. However, Victoria loved what she was doing and feels a true calling to be a teacher. All he had to say was that it was the wrong job in the wrong city; he usually condescended about her job because she can be poor. “You don’t want to be poor for the rest of your life, do you? He said with a look of condescended.” (p. 128) From the quotation above, when Victoria announced she wanted to be a teacher, her father pressures her to join him in advertising because that is where she’ll earn the most money. Her father did not agree with her decision, now, her father not only insult Victoria about her physical but also condescending about her job. Tracing the quotation above, Jim refused Victoria become a teacher, he did not sure that Victoria afford to be a teacher, and he contempt that become a teacher made she to be poor and Jim did not want to subsidize Victoria. The Causes of Victoria Dawson Mental Bullying Olweus, (2004) explained that family, especially the Parents is an important factor that has a strong influence on the development of Bullying than the environments. Ahmed and Braithwaite, (2004:36) also state that family is the most influential factor in determining a person's involvement in bullying behavior. The family is the primary socializing place for children; families also have an important role in shaping a child’s behavior. In the novel Big Girl, Victoria Dawson is a 6-year-old girl; for the first, she experienced mental bullying from her family when she was born And from people around her because she was a chubby little girl with blond hair, blue eyes, and ordinary looks. Victoria Dawson mental bullying occurs from family factor and there are two causes that made Victoria experienced Mental Bullying from family factor; Narcissistic her parents and Being Different from her Family. Narcissistic her parents A narcissist always hopes that people will respect himself in any situation, on other hand a narcissistic does not want to admit people’s greatness but always envies someone else who seems smarter, more handsome or more successful. A narcissistic tries to impede the perception of real condition so that everything which is just belonging to one’s self is highly valued and everything that belonging to another is devalued (Feist , 2002). From the explanation about Narcissistic above, the readers know about definition of narcissistic. And this one of the example causes Victoria Dawson mental bullying from family factor. In “Big Girl” Victoria Dawson is the main female character who received mental bullying because of narcissistic her parents. When Victoria twenty two years old, she go to North-western. Then she moved to New York and become an English teacher. And it made her father looked annoyed, to him; it was not even a job. He kept telling her to get a “real” job for decent money, but Victoria refused her father decisions, she still wanted to be a teacher. It can be seen from the quotation here: “I don’t want to work in advertising,” she said firmly. “I want to be a teacher.” It was the thousandth time she’d said it to him.” (p. 129) From the quotation above, we know that Victoria wanted to be a teacher, her parents belittle and mock her throughout, he disagrees with her decisions, her father forced Victoria to work in advertising because he had opinion that Victoria can not live from teacher’s salaries. Her father said that Victoria can get precious job than become a teacher, she could be making three or four times what they pay to her, at any advertising agency or in any company. Jim disapproving about Victoria decisions work to private school in New York. The conclusion that Victoria parents is a narcissistic people, they just looked from handsome or beautiful and more successful perceptions and did not care with her child opinions. Quotation above explained that Victoria sister was married to a rich man was going to be a perfect complement to her father narcissism. With her ring on her finger, Grace had become a trophy proof of his success as a father, that he raised a daughter who could marry a rich man. And it made Grace no had voice and no opinions. Gracie bought into a lot of it, their lifestyle, their opinions, their politics, and their philosophies about life. Narcissistic her parents is the causes Victoria experienced mental bullying from her parents. Being Different from her family Being different from her family is the other example of causes mental bullying from family factor that Victoria experienced. Victoria Dawson is a main female character in “Big Girl” she was born from perfect physical appearance; Jim Dawson (Victoria father) was handsome from the day he was born. . He was tall for his age, had a perfect physical. Christine Dawson (Victoria Mother) she was petite and slim with hair and eyes as dark as his, and skin like Snow White. And Grace (Victoria Sister) she really a pretty girl like her mother. When she was a year old, she grew into a beautiful baby, Grace and her parents have the same appearance but Victoria was different from her family. She was naturally a big girl, liked her paternal great-grandmother, and her breasts made her like heavier. She had an hourglass figure that would have worked well in another era. It can be seen from the quotation here: “Victoria was different; she had a square look to her, a bigger frame, and broad shoulders for a child.” (p. 28) From the quotation above, Victoria was born different with her family, both her parents and grace had thin frames, her father was tall and her mother and the baby were delicate and fine boned and had small frames. Grace and her parent have the same appearance, Victoria was different, and she look liked her grand mother that has big body. Victoria always become mockery from people around her, in her school, the teacher also mocked Victoria about her physical, Victoria feel that she really born different from her family. We can take conclusion that Victoria always feel that she was the galoshes because she had big body and she did not same with her family, her parent and sister are thin. And they like an apple, orange and banana but Victoria was always galoshes in her family and it is causes that made Victoria experienced mental bullying from her parent and people around her. The Impacts of Victoria Dawson mental bullying Bullying is a major social problem that can have serious effects on the wellbeing of young people. Many studies have suggested that greater frequency and severity of bullying is associated with poorer psychological wellbeing and with adjustment problems in later life. Difficulties later in life, such as family or workplace violence, may be more likely if the person is a bully- victim. Of the several impact of mental bullying that has been mentioned in review of related literature, which include that impacts of mental bullying that occurs in the character of Victoria is she feel sadness and self esteem. Victoria feel Sadness and self esteem; sadness is different to depression, as when people feel sad the feelings often pass in time but with depression they might not. Bullying can make people feel sad and lead to depression. People who are bullied are at more risk of depression and suicide attempts than those who are not being bullied. And Self esteem is Bullies often attack victims self esteem through verbal harassment and social exclusion. Individuals who are consistently berated and excluded by bullies may begin to believe that the bully's personal insults are true. (http://bullyingendshere.ca/EFFECTS_OF_BULLYING.html). When Victoria child, she experienced mental bullying especially from her parents. Victoria parents always embarrassed; humiliation; and condescending Victoria. In her society, Victoria also get name calling from people around her. And it made Victoria feel sadness and undermined her self-esteem, which is there are three impacts because of Victoria feel sadness and self esteem are: Search for self identity to New York Search for self identity to New York is an example from the impacts of Victoria Dawson feel sadness. Victoria Dawson always experienced mental bullying from people around her, because physical appearance. She had different physical appearance from her parent. Because her parents and people around her embarrassed, gossiping and give name calling to Victoria about physical appearance, Victoria feel suppressed and unwelcome they had made her feel for so long. Gracie was liked their only Child and she feel like the family stray dog. She did not even look like them, and she could not take it anymore. Growing up being the 'tester cake' is not easy, and even though Victoria is intelligent and ambitious, she is constantly reminded that men did not want smart girls. When Victoria finally moved out to go to college, each visit to her parents results in her dad's teasing and her mother weight-related questions. At least with her new life in New York, where Victoria is soon to be employed as a teacher, she can escaped from her family and finally start a new life in which she is accepted as who she is. Gracie had parents who worshipped and adored her, and supported her every move and decision. That was heady stuff. And she had no reason to rebel against them, or even separate from them. She did everything their father thought she should. He was her idol. And Victoria had parents who ignored her, ridiculed her, and never approved of a single move she made. Victoria had good reason to moved far away “She was willing to push herself out of her comfort zone if it meant finding herself at last, and the place where she belonged. All she knew now was that it wasn’t here, with them. No matter how hard she had tried, she just wasn’t like them.” (p.62) Victoria leaved her cruel family in Los Angeles to become an English teacher at one of Manhattan's swankest private high schools. From the quotation above, we know that Victoria wanted to push herself out of her comfort zone, to finding herself, because they always made fun of her and diminished and dismissed her. They always made her feel unwanted and not really good enough for them. So she decided to become an English teacher at New York. The conclusion from analysis about Search for self identity to New York is Victoria decided to move to New York to fulfill her dreams and escape her family. She ready to start her new life in which she is accepted as who she is. And though her new life is exciting, the old temptations remain, and she continues to wage war with the scales. Victoria struggles to find a life far from the hurt and neglect of her childhood, the damage created by her parents, the courage to find freedom, and become who she really is at last. Struggle from her Body Image Struggle from her body image is a second example of the impacts Victoria Dawson experienced mental bullying. That makes Big Girl fascinating is how it chronicles Victoria struggles with her weight. Victoria becomes known as their tester cake, an experiment allowing them to get the recipe right the second time. She receives years of put-downs from her narcissistic father, and her mother ignores the comments, often adding her own advice as to how Victoria could make more of her looks and maybe someday get a man. The main character, Victoria, struggles with her weight, body image and self-esteem from childhood. Her parents frequently criticize her and favor her younger, thinner sister. As a consequence, Victoria constantly battles her weight, trying different diets and exercise programs, only to slide back into comfort eating when her parents upset her. It can be seen from the quotation here: “The summer before Victoria entered high school she went on her first diet, she had seen an ad for an herbal tea in the back of a magazine, and sent away for it with her allowance. The ad said that it was guaranteed to make her lose ten pounds, and she wanted to enter high school looking thinner and more sophisticated than she had in middle school.” (p. 34) From the quotation above we know that Victoria Dawson had a big body and she unsatisfied with her body and she felt sad. So, she went on her first diet, she want looking thin and more sophisticated likes Victoria's sister Grace, the beautiful anger and the perfect replica of her parents is at the center of attraction in this family. We can take the conclusion that Victoria really wants struggles with her weight, Victoria parents frequently criticize her about her weight, and Victoria constantly battles her weight. Victoria really wants to look thin and reflected her family, so she did everything possible in order to lose her weight. She attempting diets, failing diets, trying at the gym, putting the weight back on, and getting therapy and surgery her nose. Finally, she gets a nose job to increase her self-worth. See a Psychiatrist People who bully others may also benefit from therapy, though they may be reluctant to acknowledge their bullying behavior openly. In therapy, bullies may begin to understand the impact their hurtful behavior has on others, explore reasons for why they bully, learn new skills for communicating positively with others, and/or address personal experiences that may have contributed to their bullying behavior. Often bullies have unresolved personal wounds that contribute to their bullying behavior, and addressing these emotional wounds or identity/social issues in therapy can be an integral step towards stopping bullying behavior. (http://www.goodtherapy.org/therapy-forbullying.html). And the last example of the impacts Victoria experienced mental bullying is she see a psychiatrist. “Big Girl” tells the story about a young woman who has been made to feel different because she does not look like her family all her life. Victoria Dawson was considered too big boned and heavy in her family and for most of her life, she was made to feel different and inadequate. She was also made to feel unloved, unlovable, and ugly. Her parents were of a different time and were very narcissistic. Her father was the kind of man who would make comments about something but make it out to be a joke, but the comments, even though joking, her mother was not much better and followed along with whatever her husband did and said. And it is hurt and would make Victoria feel like she was worth nothing for many years. When she got back to New York, she was disheartened by the things her parents had said, and the weight she had put back on, and because Harlan suggestion she see a psychiatrist. At the first time Victoria meet the psychiatrist, she asked few details about Victoria and her family background. It can be seen from quotation here: “She asked Victoria a few details about where she had grown up, where she had gone to school, and college, how many siblings she had and if her parents were still married or divorced.” (p.234) From the quotation above, we know that Victoria really see a psychiatrist because suggestion from Harlan. Although in the beginning she feel agonized and afraid, she afraid if the women discovered that she was crazy. When she asked few details about Victoria, all the question is easy to answer for Victoria, especially when she answered the question about Grace, Victoria lit up like a light bulb when she answered the question about having a sibling, and then described her and how beautiful she was. From analysis about see a psychiatrist, we can take the conclusion that Victoria feel sadness and father joke is hurt her heart. So, she see a psychiatrist because Harlan suggestion. And after she sees a psychiatrist she feels free than before, she had been entirely open and honest with her. She had a feeling that she had opened a door that afternoon and let the light into the dark corners of her heart. CONCLUSION The conclusion is divided into two in This Study is about the main female character, Victoria Dawson from the novel “Big Girl” based on the statement of the problem. In analyzing the character, this study uses Psychology of Bullying theory. There are three statements of problem; What mental bullying is experienced by Victoria Dawson in Danielle Steel’s Big Girl, What are the causes of Victoria Dawson mental bullying in Danielle Steel’s Big Girl and What are the impacts of Victoria Dawson mental bullying in Danielle Steel’s Big Girl. Those questions have been answered in the analysis. Victoria Dawson mental bullying is the main topic has been explained detail based on the theory above. As explained in the review of related literature there are several kind of mental bullying, But of the several kinds mental bullying that have been mentioned, which includes the kinds of mental bullying that depicted to Victoria Dawson mental bullying are; Humiliation, Embarrassed and Condescended. And the first explanation has used those three kinds of mental bullying to analyzing Victoria Mental Bullying. As seen in the novel, Victoria Dawson as the main character, she experienced mental bullying from her parents and people around her because different physical appearance than her family. Victoria parents were born from perfect physical appearance. Her father, mother and sister have the same appearance, but Victoria was different. When Victoria was a child, she experienced mental bullying from people around her and especially from her parents and three kind of mental bullying that have been mentioned its occurs to Victoria Dawson. In the second explanation, this study discusses about the causes of Victoria Dawson mental bullying. The causes of Victoria Dawson mental bullying its come from Family factor, There are two causes that made Victoria experienced Mental Bullying from family factor; Narcissistic her parents and Being Different from her Family. Victoria Dawson is a 6-year-old girl; for the first, she experienced mental bullying from her family when she was born And from people around her because she was a chubby little girl with blond hair, blue eyes, and ordinary looks, Victoria Dawson has always felt out of place in her family, because narcissistic her parents and she was being different from her family especially in body-conscious. And the last explanation discusses about the Impact of Victoria Dawson Mental Bullying. The impacts of Victoria Dawson mental bullying its she feel sadness and self esteem which is there are three impacts because of Victoria feel sadness and self esteem; Search for Self Identity to New York, Struggle from her Body Image, and See a Psychiatrist. Mental Bullying that Victoria experienced from her parents and people around her brings many impacts to Victoria, She feel sad, not confident and lonely. So, she decided to search self identity to New York, Struggle from her body and See a Psychiatrist to fulfil her dream, raised her self esteem and wants to look thin and reflected with her family. REFERENCE Ahmed, E. & Braithwaite, V. (2004). Bullying and Victimization. Causes of Concern for Both Families and Schools. Cambridge: Cambridge University Press. Beane, A. (1999). Facts about bullies/victims and preventive advice. United States: Free Spirit Publishing Inc. Beane Allan L., Ph.D. (2003). Bully Free Program. Helpful Fact Sheets for Parents. United States: Free Spirit Publishing Inc. DeHaan, Laura Ph.D. (2009). Bullies. United States: NDSU. Elliot, Michele. (2005). Bullying Wise Guides. New York: Hodder Children’s Books. Feist, Jess, and Gregory J. Feist. (2002). Theories of Personality 5th ed. Boston: MC Graw Hall. Olweus, Dan. (1993). Bullying at School. What we know and what we can do. London: Blackwell Publishing. Olweus, Dan. (2004). Bullying at School. London: Blackwell Publishing. Sejiwa. (2007). Bullying panduan bagi orang tua dan guru. Jakarta: Grasindo. Steel, Daniell. (2010). Big Girl. United States: Delacorte Press Publisher. Sullivan, Keith. (2000). The Anti Bullying Handbook. London: Oxford University. Internet Source: (http: Bullyingendshere.ca/ Effect of Bullying. Html) Accessed in 14th 2013 (http: Selfishness and Narcissism in Family Relationships - article by Dr. Lynne Namka.html) Accessed in February 2013 (http: Goodtherapy.org) Accessed in 12th 2013 (http: What causes bullying.html) Accessed in 11th 2014